1996
DOI: 10.1097/00004647-199601000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Elevation of Extracellular Neurotransmitter Amino Acids in the Reperfusion Phase following Focal Cerebral Ischemia

Abstract: The purpose of this study was to evaluate amino acid neurotransmitter dynamics in the reperfusion phase after transient cerebral ischemia. In vivo microdialysis was used to measure extracellular amino acid levels in a rabbit model of focal ischemia. During 30 min of transient ischemia (n = 5), small but significant (p < 0.05) increases in glutamate, aspartate, gamma-aminobutyric acid (GABA), and taurine were noted. These elevations rapidly returned to baseline levels upon recirculation and remained constant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 51 publications
8
58
0
1
Order By: Relevance
“…In vivo studies showed a recovery of glutamate release to the baseline during reperfusion (Torp et al 1993); however, in other studies a transient further increase in the release of glutamate was found in the initial phase (Taguchi et al 1996;Caragine et al 1998) or after hours of reperfusion (Matsumoto et al 1996;Yang et al 2001). In addition, in vivo neuroprotection exerted by NMDA and non-NMDA receptor antagonists, even when added after the initiation of a transient ischemia (Park et al 1988;Sheardown et al 1990;Nellgard and Wieloch 1992) suggested that glutamate neurotransmission could also be important after the ischemic attack, during reperfusion (see also Nishizawa 2001).…”
Section: Discussionmentioning
confidence: 94%
“…In vivo studies showed a recovery of glutamate release to the baseline during reperfusion (Torp et al 1993); however, in other studies a transient further increase in the release of glutamate was found in the initial phase (Taguchi et al 1996;Caragine et al 1998) or after hours of reperfusion (Matsumoto et al 1996;Yang et al 2001). In addition, in vivo neuroprotection exerted by NMDA and non-NMDA receptor antagonists, even when added after the initiation of a transient ischemia (Park et al 1988;Sheardown et al 1990;Nellgard and Wieloch 1992) suggested that glutamate neurotransmission could also be important after the ischemic attack, during reperfusion (see also Nishizawa 2001).…”
Section: Discussionmentioning
confidence: 94%
“…We did not explore the therapeutic window for DCPIB, yet further studies would be useful to establish the actual therapeutic window to show this correlates only with inhibition of the early transient increased EAAs, or a broader therapeutic window is found consistent with later smaller secondary increases in EAAs seen after reperfusion (Matsumoto et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The secondary rise in cortical glutamate concentration corresponds to that in the level of seizure activity. Matsumoto et al (30) reported that the large secondary elevation in concentrations of transmitter amino acids occurred in the reperfusion phase after 2 h of transient focal ischemia in a rabbit model. They found correlations between primary (ischemic) and secondary (reperfusion) transmitter interstitial levels, suggesting that secondary elevations are 278 related to the severity of the primary insult.…”
Section: Discussionmentioning
confidence: 99%